Subcutaneous Pancreatic Transplantation Shows Success In The Treatment Of Experimentally Induced Diabetes Mellitus In Golden Hamsters - Al-Shaik, Mahera N; Al-Khateeb, Huda M; Al-Ubaidy, Salim R (Journal of the Faculty of Medicine Baghdad, 2006)
Background: to evaluate subcutaneous pancreatic transplantation in an experimentally induced diabetes mellitus in golden hamsters.Methods - many indexes (histological /using two stains, histochemical /using three enzymes, morphometrical and biochemical /blood glucose level) were employed in this assessment. Alloxan was used as ß-cytotoxic therapy (to induce diabetes mellitus), and cyclophosphamide was employed as immunosuppressive agent.Results - high rate of success of transplantation (clearly evident by microscopical features of viable endocrine and exocrine tissue of transplanted pancreas and great tissue vascularization, normal enzymatic activities and significant lowering of blood glucose level) were elicited.Conclusion – subcutaneous pancreatic transplantation should be thank about in treatment of diabetes mellitus.